UMPSA collaborates with Elsevier, first public university in Malaysia to access ‘Scival’ to increase impactful publication reach - Naqiah, Puaad (UMPSA, 2025)
PUTRAJAYA, 3 September 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is the first public university (UA) in Malaysia to subscribe to ‘SciVal’, a Scopus data-based analytical tool, as a facility for the university’s lecturers and students to enhance reach that brings impact to the university’s research ecosystem at the international level.